Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.108.174.1989
|View full text |Cite
|
Sign up to set email alerts
|

First Palynological Results from Site 658 at 21°N off Northwest Africa: Pollen as Climate Indicators

Abstract: Ocean Drilling Program Site 658 at 21°N off northwest Africa has a high sedimentation rate and a high concentration of pollen grains and is thus very suitable for detailed pollen analysis. The time scale for the upper 100 m (the last 670 k.y.) of Site 658 is based on biostratigraphic data and isotope stratigraphy. The pollen record has been divided into 34 zones. These are classified into 7 zone types covering a range from very arid to rather humid conditions. The sequence shows a long-term climatic decline: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The concentration of pollen in Neogene sediments from Holes 794A, 795A, and 797B in the Sea of Japan is high, comparable to pollen concentration in Japanese bogs (Tsukada, 1967) and exceeding that reported from piston cores and ODP cores in the Arabian Sea and the North Pacific and Atlantic oceans (Heusser, 1977;Van Campo, 1986;Dupont, 1989). The highest pollen concentrations in samples from these three Japan Sea sites are similar to those from Site 565 in the equatorial eastern Pacific, which is very close (-42 km) to land (Horn, 1985).…”
Section: Summary Evaluation Of Pollen In Holes 794a 795a and 797bsupporting
confidence: 53%
“…The concentration of pollen in Neogene sediments from Holes 794A, 795A, and 797B in the Sea of Japan is high, comparable to pollen concentration in Japanese bogs (Tsukada, 1967) and exceeding that reported from piston cores and ODP cores in the Arabian Sea and the North Pacific and Atlantic oceans (Heusser, 1977;Van Campo, 1986;Dupont, 1989). The highest pollen concentrations in samples from these three Japan Sea sites are similar to those from Site 565 in the equatorial eastern Pacific, which is very close (-42 km) to land (Horn, 1985).…”
Section: Summary Evaluation Of Pollen In Holes 794a 795a and 797bsupporting
confidence: 53%
“…Nevertheless, obliquity (41 kyr) cycles have also been detected in sequences of Mediterranean sapropels (Lourens et al, 1996), which formation depends on monsoonal freshwater discharge from Africa (Rossignol-Strick, 1983;Colleoni et al, 2012;Larrasoaña et al, 2013). Equally, dust flux rates at Ocean Drilling Program (ODP) Site 659 (Tiedemann et al, 1994) and pollen flux rates at ODP Site 658 (Dupont et al, 1989) show obliquity cycles in records of tropical Africa, which are difficult to explain, since obliquity has a negligible effect on lowlatitude insolation (Laskar, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Höleman and Henrich, 1994;Combourieux-Nebout et al, 2000). From isotopic curves, notable cold phases started around 600 ka (Dupont et al, 1989;Shackleton et al, 1991) with intense glacial stages were only found after 480 ka (OIS 12). In Britain (Worsley, 1987) and Brittany (Van Vliet-Lanoë et al, 1997), the oldest true ice wedge casts probably correlate with OIS 12 (420 -480 ka BP) and 10 (340 -360 ka BP).…”
Section: Discussionmentioning
confidence: 98%